Subjective Workload Assessment among Nurses and Its Relationship with Work Quality Satisfaction: A Scoping Review - Yulia Misni; Nurfika Amaningrum; Muhamad Zulfatul A'la (GLOBAL HEALTH SCIENCE GROUP, 2025)
Subjective Workload Assessment among nurses is a crucial aspect in evaluating the well-being of healthcare professionals and the quality of care provided. High workload levels have been associated with increased stress, burnout, and decreased job satisfaction, ultimately affecting the quality of healthcare services. Additionally, organizational factors such as uneven workload distribution, inflexible work schedules, and limited social support further exacerbate the negative effects of excessive workload. Therefore, a comprehensive review is necessary to understand how subjective workload influences job satisfaction and how social support-based interventions can mitigate its adverse effects. This scoping review aims to identify and analyze the relationship between subjective workload assessment, social support, and job satisfaction among nurses in non-intensive care units. A systematic literature search was conducted across PubMed, Scopus, Web of Science, and the Cochrane Library, with a publication date range from 2020 to 2024. Article selection was based on the Population, Concept, Context (PCC) framework developed by the Joanna Briggs Institute (JBI). Out of 228 identified articles, 45 passed the initial screening phase. Following a critical appraisal using the Joanna Briggs Institute Critical Appraisal Tools, 12 studies met the final inclusion criteria. The reviewed studies employed quantitative, qualitative, and mixed-methods approaches, investigating subjective workload in nurses and its relationship with job satisfaction and social support. Literature analysis indicates that high subjective workload is associated with decreased job satisfaction, increased stress, burnout, and negative impacts on nurses’ mental health. Studies further reveal that peer support is more effective in alleviating workload-related stress compared to support from supervisors or management. Additionally, a supportive work environment and flexible organizational policies contribute to higher job satisfaction despite high workload levels. However, challenges persist in implementing workload evaluation strategies, particularly due to the lack of standardized assessment frameworks and the limited availability of longitudinal research examining the long-term effects of subjective workload on nurses’ well-being. High subjective workload has significant negative effects on nurses' mental well-being and job satisfaction. However, peer support, flexible organizational policies, and evidence-based interventions can mitigate the adverse effects of excessive workload. Therefore, further research is needed to explore more effective intervention strategies for improving nurses' well-being. This review also recommends the development of inclusive policies and standardized workload assessment frameworks to ensure that healthcare professionals can deliver optimal care in a healthier and more supportive work environment.